59.3k views
1 vote
Help!


\sf √(x-2)-x=-2

2 Answers

3 votes

Answer:


\sf\longmapsto \: x = 3

Explanation:


\sf\longmapsto \: √(x - 2 ) - x = - 2


\sf\longmapsto \: √(x - 2) = x - 2


\sf\longmapsto \: 1 = (x - 2)/( √(x - 2) )


\sf\longmapsto1 = √(x - 2)


\sf\longmapsto \: x - 2 = 1


\sf\longmapsto \: x = 3

User Lanery
by
5.4k points
4 votes


▪▪▪▪▪▪▪▪▪▪▪▪▪  {\huge\mathfrak{Answer}}▪▪▪▪▪▪▪▪▪▪▪▪▪▪

Let's solve for x :


  • √(x - 2) - x = - 2


  • √(x - 2) = x - 2


  • 1 = (x - 2)/( √(x - 2) )


  • 1 = √(x - 2)


  • x - 2 = 1


  • x = 3
User Sreenath S
by
5.6k points